Effect of Methyl Ethyl Ketone (MEK) Organic Solvent Exposure on Incidence of Neurotoxicity in Shoe Manufacturing Workers - Denta Aditya Episana; Aria Kekalih; Liem Jen Fuk (ILUNI MKK FKUI and PRODI MKK FKUI, 2021)
Background: Shoe manufacturing factory workers in developing countries are daily exposed to complex mixtures of organic solvents. Chemical exposure occurs through inhalation / respiration and skin which can affect many physiological systems. The main chemical exposure to organic solvents in shoe manufacturing comes from the process of gluing and cleaning process by using organic solvents on footwear in the assembling section. Methyl ethyl ketone is one type of organic solvent which, when entering into the body through inhalation routes can cause irritation of the nose, throat, lungs and chest becomes congested. Acute neurotoxicity is a collection of symptoms in the central nervous system (central nervous system depression, psychomotor disorders, narcosis, drowsiness, headache, dizziness, dyspepsia, and nausea). Method: The research design was a prospective cohort research consisting of 45 people for each high MEK exposed group and low exposed to MEK. Data collection was done by interview, physical examination, MEK level measurement of pre-shift urine and end-shift work, and filling out questionnaires Form Acute symptoms rating questionnaire at the beginning of work shift (07.00), 2 hours after work (09.00), break (12.00), 2 hours after break (15.00), and end of work shift (16.00). Result: The incidence of acute neurotoxicity symptoms in the MEK-high exposed group based on the Acute Symptoms questionnaire was 51.1%. Age factor with symptoms of acute neurotoxicity in workers at PT. X with p value = 0.432, gender factor with p value = 0.162, education factor with p value = 0.897, nutritional status factor with p value = 0.865, alcohol habit factor with p value = 0.181, coffee drinking habit factor with p value = 0.265, and smoking habit factor with p value = 0.968, work duration factor with symptoms of acute neurotoxicity at worker in PT. X with p value = 0.533, and the use factor of personal protective equipment (PPE) with p value = 0.470. In this research, symptoms of acute neurotoxicity were dominant are fatigue (80%), headache (77.8%), nausea (71.1%), dizziness (66.7%), and feeling of intoxication (53.3%). Conclusion: There are no subject and occupational factors that have a significant effect to the symptoms of acute neurotoxicity. Conducting isolation of other work areas for workers exposed to chemicals that because of high potential to harm other workers in the vicinity. Reassessing the hazard risk of using MEK substitutes with other chemicals that are of lower risk or replace with water-based solvents. Provide PPE eligible to all workers exposed to chemicals and workers around them. A PPE fit test is used for workers to feel comfortable while wearing it, giving strict sanctions to workers who do not consistently use personal protective equipment.